ICT and Non-ICT investments: short and long run macro dynamics - Fabio Bacchini; Maria Elena Bontempi; Roberto Golinelli; Cecilia Jona Lasinio (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2014)
In this paper, we model business investment distinguishing between ICT (communication equipment, hardware and software) and Non-ICT (machinery and equipment, and nonresidential buildings) components and taking into account asset specific characteristics potentially affecting the reactivity of capital accumulation over the business cycle. Business investment and ICT and Non-ICT assets are estimated within a VECM model to test, in a unique framework, the assumptions of the flexible accelerator model (Clark, 1944, and Koyck, 1954) and of the neoclassical model of Hall and Jorgenson (1967), as well as how financial constraints and uncertainty influence investment behaviour (Hall and Lerner, 2010, and Bloom, 2007). Our findings suggest that the long-run relationship with standard macro determinants (output and user cost) is verified for aggregate business capital stock as well as for individual Non-ICT assets but not for ICT. In the short run, liquidity is a key determinant of investment behaviour independently of the asset type. In the long-run, uncertainty significantly affects ICT. Finally, the results of the counterfactual exercises over the latest Italian recession support the idea that ICT is a key policy variable to foster the economic recovery.
Keywords: C52; C53; E22; E50; 330